Pollution potential of solid wastes from Elazig ferrochrome and Keban zinc-lead plants - Tumen, F.; Boybay, M.; Solmaz, B.; Cici, M.; Bildik, M. (My University, 1991)
In this study, the potential of heavy metal pollution of solid wastes produced from Elazig ferrochrome and Keban zinc-lead plants were investigated. The metal pollution caused by the wastes was explored by column tests for one year. As a result of percolating tests carried out both systematically and in open atmosphere, the flotation tailings from the zinc-lead concentration plant were found to be the most important metal pollutants. The maximum concentrations of Cd, Cu, Co, Fe, Mn, Ni and Zn in the leachate of this waste were determined as 23.23, 5.70, 36.06, 3375, 500, 10.65 and 6343 mg/l. -from English summary
Elazig ferrokrom fabrikasi ve Keban simli-kursun isletmesi kati atiklarinin kirlilik potansiyeli
Keywords: Elazig; Kebab; Turkey; flotation tailings; heavy metal; leaching; pollution; soil